Ephemeron : Poems - Hummer, T. R. (Book collections on Project MUSE., 2012)
In a work of startling originality, the T.R. Hummer's Ephemeron presents a meditation on ephemerality from the point of view of the ephemeron itself as it passes, be it the individual, the atom, the particle. Relentless in its stalking of the boundary between being and nonbeing, Hummer's work becomes a tour-de-force that shines a spotlight into dark corners of Being, revealing yet more darkness.